2021
DOI: 10.1016/j.foostr.2020.100173
|View full text |Cite
|
Sign up to set email alerts
|

Modulating process parameters to change physical properties of bigels for food applications

Abstract: The effect of the process parameters involved in the production of bigels was investigated through the study of structural, mechanical and rheological properties. Four level (2 4) Central Composite Rotational Design (CCRD) configuration was applied in order to study the organogelator concentration, hydrocolloid concentration, organogel:hydrogel ratio and shear of mixing. Gellan gum and high oleic sunflower oil with glycerol monostearate were used to produce hydrogels and organogels, respectively. All formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 47 publications
(70 reference statements)
4
25
0
Order By: Relevance
“…With regard to the rheological properties, all samples revealed a typical gel network formation as the elastic modulus (G′) was always above the loss modulus (G″) and both moduli were separated by less than one logarithmic cycle (with the tan δ always below 1) ( Figure 6 ). Such behaviour was previously reported as typical for gels and spreads [ 31 , 38 , 39 ]. Additionally, a slight frequency dependence was observed for both moduli, suggesting that although the gels were strong, they showed a slightly weak network.…”
Section: Resultssupporting
confidence: 73%
“…With regard to the rheological properties, all samples revealed a typical gel network formation as the elastic modulus (G′) was always above the loss modulus (G″) and both moduli were separated by less than one logarithmic cycle (with the tan δ always below 1) ( Figure 6 ). Such behaviour was previously reported as typical for gels and spreads [ 31 , 38 , 39 ]. Additionally, a slight frequency dependence was observed for both moduli, suggesting that although the gels were strong, they showed a slightly weak network.…”
Section: Resultssupporting
confidence: 73%
“…In the images of bigels, the needle-like structure of BW cannot be easily seen as in the BW-O. This fact could suggest that the shear in the bigel preparation process may destroy the more ordered structure of the BW of oleogel or that the BW crystals would dissipate with the aqueous content within the mixture in accordance with what was found by Martins et al [ 3 ] and Fasolin et al [ 11 ] for bigels.…”
Section: Resultssupporting
confidence: 71%
“…Other authors have reported different effects of mixing the two phases of bigels, changing the rheological behavior and mechanical properties of the original matrices, where the bigel components lead to changes in network strength; these changes could be related to interactions between the disperse and continuous phases [ 11 ]. For example, in bigels prepared with medium-chain triglycerides Neobee-beeswax (3 and 6%) oleogel and ALG hydrogel (at 2%), mixed at 600 rpm, the oleogel fraction disrupted the alginate network (forming oleogel-in-hydrogel matrix) and consequently decreased the mechanical properties of the bigels compared to the ALG hydrogel; however, the firmness of bigels was higher than that of the original oleogels [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations